Comparative analysis of extracted chitosan versus commercial one: physiochemical effects of extraction - DEHANE, Aicha (Biopolymer Applications Journal, 2025)
This study successfully extracted chitosan from waste generated by local shrimp shells. Functional and physicochemical properties of Chitosan produced have been evaluated by several methods such as FTIR, XRD and DSC. The obtained chitosan showed similar physicochemical properties compared to commercial one prepared. Structure was confirmed by Fourier transform infrared spectroscopy; X-ray diffraction and differential scanning calorimeter have same differences to refer to the effect of methods of extractions and type of shrimp shells waste.